2020
DOI: 10.1093/mnras/staa630
|View full text |Cite
|
Sign up to set email alerts
|

X-ray, UV, and optical time delays in the bright Seyfert galaxy Ark 120 with co-ordinated Swift and ground-based observations

Abstract: We report on the results of a multiwavelength monitoring campaign of the bright, nearby Seyfert galaxy, Ark 120 using a ∼50-day observing programme with Swift and a ∼4-month co-ordinated ground-based observing campaign, predominantly using the Skynet Robotic Telescope Network. We find Ark 120 to be variable at all optical, UV, and X-ray wavelengths, with the variability observed to be well-correlated between wavelength bands on short timescales. We perform cross-correlation analysis across all available wavele… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 64 publications
3
14
0
Order By: Relevance
“…For instance, Porquet et al (2018Porquet et al ( , 2019 used broad-band spectral modelling and found strong indications for the presence of a warm, opticallythick corona, which may be extended, in Ark 120. This may have relevance to the observed time lags, which were reported by Lobban et al (2020) to be larger than expected from standard disc theory (while remaining consistent with the τ ∝ λ 4/3 relation, similar to NGC 5548). If such a warm corona, with a large optical depth exists, then all the UV/optical photons emitted by the underlying disc will be scattered to soft X-rays.…”
Section: Physical Interpretation Of Frs Resultssupporting
confidence: 78%
“…For instance, Porquet et al (2018Porquet et al ( , 2019 used broad-band spectral modelling and found strong indications for the presence of a warm, opticallythick corona, which may be extended, in Ark 120. This may have relevance to the observed time lags, which were reported by Lobban et al (2020) to be larger than expected from standard disc theory (while remaining consistent with the τ ∝ λ 4/3 relation, similar to NGC 5548). If such a warm corona, with a large optical depth exists, then all the UV/optical photons emitted by the underlying disc will be scattered to soft X-rays.…”
Section: Physical Interpretation Of Frs Resultssupporting
confidence: 78%
“…We find that in XMM1 observation, there is no delay between the low and high energy band, while a positive delay of 4.71 ± 1 ks is detected in XMM2 observation and a negative delay of 4.15 ± 1 ks is seen in XMM3 observation. A correlated variability among the optical, UV, and X-ray bands have already been reported Lobban et al (2020). Also, (Dutta & Chakrabarti 2016;Chatterjee et al 2017b) reported in a different context that the X-ray lag has a strong dependency on the geometric structure of the Comptonization region and orientation of the Keplerian disc.…”
Section: Discussionmentioning
confidence: 67%
“…The diagram for lag against ZDCF value of the sample blazars are shown in Figure 4. The lag between the emissions was estimated by computing the centroid of the ZDCF peak, i. e., τ c = i τ i ZDCF i / i ZDCF i , where τ c is calculated using the ZDCFs around the DCF peak that are greater than 0.8 times the ZDCF peak value (see e. g. Lobban et al 2020;Buisson et al 2017). A positive lag implies γ-ray variability features preceding those in the optical observations.…”
Section: Cross-correlation Between the Optical And The γ-Ray Bandmentioning
confidence: 99%